2020
DOI: 10.1016/j.aop.2020.168098
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous features of non-Hermitian topological states

Abstract: Topological states in non-Hermitian systems are known to exhibit some anomalous features. Here, we find two new anomalous features of non-Hermitian topological states. We consider a one dimensional nonreciprocal Hamiltonian and show that topological robustness can be practically lost for a linear combination of topological eigenstates in non-Hermitian systems due to the non-Hermitian skin effect. We consider a two dimensional non-Hermitian Chern insulator and show that chirality of topological states can be br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…This implies that weak disorder can induce transition among the eigenstates clustered in the same group. This leads to the breakdown of chirality of topological states in 2D as dis-cussed by our earlier paper [35]. This is because of the fact that propagation of topological state is supported in only one direction in an Hermitian 2D strip, since no state is available at the same energy that propagates in the opposite direction on the same edge.…”
Section: Examplesmentioning
confidence: 90%
“…This implies that weak disorder can induce transition among the eigenstates clustered in the same group. This leads to the breakdown of chirality of topological states in 2D as dis-cussed by our earlier paper [35]. This is because of the fact that propagation of topological state is supported in only one direction in an Hermitian 2D strip, since no state is available at the same energy that propagates in the opposite direction on the same edge.…”
Section: Examplesmentioning
confidence: 90%
“…However, both of them as well as bulk eigenstates are localized around the left edge due to the non-Hermitian skin effect. In our recent paper [15], we showed that a zero-energy mode at the right edge can still be available, but it tends to move rapidly to the left edge.…”
Section: Non-topological Robust Zero-energy Edge Statesmentioning
confidence: 93%
“…We show that the dispersion relations given in Eqs. (56), (57), (60), and (61) are valid even when |ρ 1 | < 1 < |ρ 2 | does not hold. In our system, the condition of 1 < |ρ 2 | widely holds but the condition of |ρ 1 | < 1 breaks down with increasing γ.…”
Section: Appendixmentioning
confidence: 99%